Fluticasone furoate demonstrates efficacy in patients with asthma symptomatic on medium doses of inhaled corticosteroid therapy: an 8-week, randomised, placebo-controlled trial. Issue 1 (9th August 2011) - Busse, William W; Bleecker, Eugene R; Bateman, Eric D; Lötvall, Jan; Forth, Richard; Davis, Angela M; Jacques, Loretta; Haumann, Brett; Woodcock, Ashley
Abstract : Background: Fluticasone furoate (FF) is a novel inhaled corticosteroid with 24 h activity. FF is being developed as a once-daily treatment in combination with the long-acting β2 agonist vilanterol trifenatate for asthma and chronic obstructive pulmonary disease. Objectives: To determine the optimal dose(s) of FF for treating patients with asthma. Methods: An 8-week multicentre, randomised, double-blind study. 627 patients with persistent moderate-to-severe asthma, symptomatic on medium-dose inhaled corticosteroid therapy, were randomised to placebo, FF 200, 400, 600 or 800 μg (once daily in the evening using a novel dry powder inhaler), or fluticasone propionate 500 μg twice daily (via Diskus™/Accuhaler™). The primary efficacy measure was mean change from baseline in pre-dose evening forced expiratory volume in one second (FEV1 ). Other endpoints included morning and evening peak expiratory flow, and rescue/symptom-free 24 h periods. Results: Each dose was significantly superior to placebo for the primary endpoint (p<0.001) with efficacy at least similar to that reported with fluticasone propionate. There was no dose–response relationship across the FF doses studied. Peak expiratory flow improved in all groups (p<0.001 vs placebo), and there were significant treatment effects on rescue/symptom-free 24 h periods with all active treatments. FF was generally well tolerated. The incidence of oral candidiasis was higher with FF 800 μg than placebo; pharmacokinetic and 24 h urinary cortisol analyses confirmed a higher systemic exposure of FF at this highest dose level. Conclusions: FF doses <800 μg have a favourable therapeutic index. The absence of an efficacy dose response suggests that 200 μg is an appropriate dose in patients with moderate persistent asthma. ClinicalTrials.gov identifier: NCT00603746.